Impact of the European Integration Processes on Internationalization of Small and Medium-sized Enterprises - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2006)
Internationalisation of small and medium sized enterprises (SMEs) may develop in different ways. One is a traditional, gradual transition through successive phases of internationalisation (a step-by-step process, like ‘rings in the water’).The other one has been labelled „Born Globals”. The foreign market entry choice open to SMEs may include: export activities, co-operation and foreign direct investment (FDI). This choice is determined by the assets and competitive advantages a given SME holds. The aim of this chapter is to examine the interrelationship between internationalization of SMEs and the European integration processes. Special attention will be paid to FDI as a form of SME internationalization in the new member countries.